Microplastics Emission from Eroding Wind Turbine Blades: Preliminary Estimations of Volume - Leon Mishnaevsky; Antonios Tempelis; Yauheni Belahurau; Nicolai Frost-Jensen Johansen (Energies)
The erosion of wind turbine blades is one of the most frequently observed mechanisms of wind turbine blade damage. In recent months and years, concerns about high volumes of eroded plastics and associated pollution risks have surfaced on social networks and in newspapers. In this scientific paper, we estimate the mass of plastic removed from blade surface erosion, using both a phenomenological model of blade erosion and the observed frequency of necessary repairs of blades. Our findings indicate that the mass of eroded plastic ranges from 30 to 540 g per year per blade. The mass loss is higher for wind turbines offshore (80–1000 g/year per blade) compared to onshore (8–50 g/year per blade). The estimations are compared with scientific literature data and other gray literature sources. Using the entire Danish wind farms portfolio, we quantify the yearly mass of plastic from blade erosion to be about 1.6 tons per year, which is an order of magnitude less than that from footwear and road marking and three orders of magnitude less than that from tires. While the contribution of wind blade erosion is small compared to other sources, the results of this work underline the importance of the (A) effective leading-edge protection of wind turbines, (B) regular and efficient maintenance, and (C) the optimal selection of materials used.